Financial derivatives : a blessing or a curse? - Grima, Simon; Thalassinos, Eleftherios (Emerald Publishing, 2020)
Should we fear financial derivatives, or embrace them? Finance experts Simon Grima and Eleftherios I. Thalassinos explore what financial derivatives are, and whether the investment world should consider them useful tools, or a complete waste of time and money.